Analisa Kegiatan Marketing Public Relations Warung Wakaka untuk Menjalin Hubungan dengan Investor - Thendian, Nicholas; Utami, Lusia Savitri Setyo (Prologia, 2022)
The development of the food and beverage industry in Indonesia is growing from year to year, making the company's competitiveness even tighter. This makes many companies create new innovations in developing Food and Beverage. Warung Wakaka is one of the food and beverage companies in Indonesia. Warung Wakaka in running its business applies marketing public relations which functions to improve investor relations and increase consumer buying interest to come to Warung Wakaka. This research uses an approach approach with the method of interview, observation, and documentation. After conducting interviews, observations and documentation of the results obtained, Warung Wakaka runs 6 of 7 benchmarks for marketing public relations activities. Six ways to measure marketing public relations activities include Publications (Publications), Identity Media (Identity Media), Events (Events), News (News), Public service activities (Public Service Activities), Sponsorship (Sponsorship). The six ways to measure the marketing public relations activities were successfully carried out by Warung Wakaka. From the results of the study, it can be said that investors have the concept of Warung Wakaka, the service, and planning run by Warung Wakaka are considered attractive. Perkembangan industri makanan dan minuman di Indonesia yang semakin berkembang dari tahun ke tahun, membuat daya saing perusahaan semakin ketat. Hal ini membuat banyak perusahaan menciptakan inovasi baru dalam mengembangkan Food and Beverage. Warung Wakaka merupakan salah satu perusahaan makanan dan minuman yang ada di Indonesia. Warung Wakaka dalam menjalankan bisnisnya menerapkan marketing public relations yang berfungsi sebagai meningkatkan investor relations serta meningkatkan minat beli konsumen untuk datang ke Warung Wakaka. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara, observasi, dan dokumentasi. Setelah melakukan wawancara, observasi dan dokumentasi hasil yang didapatkan yaitu Warung Wakaka menjalankan 6 dari 7 cara tolok ukur kegiatan marketing public relations. Enam cara tolak ukur kegiatan marketing public relations diantaranya Publications (Publikasi), Identity Media (Media Identitas), Event (Acara), News (Berita), public service activities (Kegiatan Pelayanan Publik), Sponsorship (Sponsor). Enam cara tolok ukur kegiatan marketing public relations tersebut berhasil dilakukan Warung Wakaka. Dari hasil penelitian dapat disimpulkan bahwa, investor bermitra dengan Warung Wakaka karena konsep, pelayanan, dan planning yang dijalankan Warung Wakaka dianggap menarik.